Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Solve: 3x+1 over 6x-2 = 2x+5 over 4x-13?
7 Answers
- 7 years ago
Here is the process:
Cross multiply:
(3x+1)/(6x-2)= (2x+5) (6x-2)
12x^2-39x+4x-13= 12x^2-4x+30x-10
-35x-26x-3=0
Value Of x= -3/61
- Anonymous7 years ago
X=3/77
- Anonymous7 years ago
(3x+1) / (6x-2) = (2x+5) / (4x-13);
(3x+1)*(4x-13) = (2x+5)*(6x-2);
expand both sides:
12(x^2) - 35x -13 = 12(x^2) + 26x -10;
or
61x=-3;
x= -3/61 <---- answer
- PolyhymnioLv 77 years ago
First, cross multiply
(3x + 1)(4x - 13) = (2x + 5)(6x - 2)
12x² - 35x - 13 = 12x² + 26x - 10
61x = -3
x = -3/61
- How do you think about the answers? You can sign in to vote the answer.
- BullwinkleLv 77 years ago
(3x + 1) / (6x - 2) = (2x + 5) / (4x - 13)
cross multiply...
(6x - 2)(2x +5) = (3x + 1)(4x - 13)
expand...
12x^2 + 26x - 10 = 12x^2 - 35x - 13
combine like terms and solve...
61x = - 3
x = - 3/61
- ?Lv 77 years ago
(3x+1) / (6x-2) = (2x+5) / (4x-13)
(3x+1)(4x-13) = (2x+5)(6x-2)
12x^2 - 35x - 13 = 12x^2 + 26x - 10
-61x = 3
x = -3/61 << answer
- Anonymous7 years ago
yes